2002
DOI: 10.1182/blood-2002-05-1406
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulinlike growth factor is not elevated in patients with multiple myeloma but is still a prognostic factor

Abstract: Insulinlike growth factor 1 (IGF-1) has growth-promoting effects on myeloma cells in vitro as well as in vivo. In this study, we measured the concentration of IGF-1 and its major binding protein, IGFbinding protein 3 (IGFBP-3), in serum from 127 patients with multiple myeloma. Serum had been drawn at the time of diagnosis, before treatment with highdose melphalan. IGFBP-3 in myeloma patients (1.6 ؎ 0.73 g/mL; mean ؎ SD) was significantly decreased compared to healthy age-and sex-matched controls (2.2 ؎ 0.42 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 30 publications
3
46
0
6
Order By: Relevance
“…Our gene expression-based results are in agreement with previous studies measuring IGF-1R and IGF-1 protein levels by flow cytometry and ELISA respectively, 7,9 showing good concordance between gene expression and protein data. While Letters to the Editor the absolute difference in gene expression level of IGF-1R among patients with different TC classes and D13 status is small, this can be accounted for by the log-transformation and normalization of gene expression data.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Our gene expression-based results are in agreement with previous studies measuring IGF-1R and IGF-1 protein levels by flow cytometry and ELISA respectively, 7,9 showing good concordance between gene expression and protein data. While Letters to the Editor the absolute difference in gene expression level of IGF-1R among patients with different TC classes and D13 status is small, this can be accounted for by the log-transformation and normalization of gene expression data.…”
supporting
confidence: 81%
“…Our results fail to confirm the prognostic importance of IGF-1R and IGF-1 suggested by other investigators. 7,9 This may be due to differences in the study population, the relatively shorter follow-up in our cohort or the sample size, and the limited number of events. However, it is important to note that powerful prognostic factors like t(4;14), t(14;16), D13 (Figure 2c and d) and plasma cell labeling index (data not shown) already demonstrate statistically significant prognostic impact in our cohort despite the relatively short follow-up, suggesting that IGF-1 and IGF-1R expression levels are unlikely to have important prognostic impact.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This cytokine confers multiple drug resistance on myeloma cells (25,30). Importantly, clinical studies have revealed that increases in serum IGF-1 levels may be correlated with poor outcomes of multiple myeloma (37). IGF-1 is also known to activate HIF-1 in several cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the same study, higher IGF-I levels were associated with poorer myeloma survival. 78 Given the relationship between insulin and IGF, it is also important to point out a meta-analysis of studies looking at the association between type 2 diabetes mellitus and myeloma demonstrated nonsignificant increased odds of myeloma in patients with type 2 diabetes mellitus (odds-ratio = 1.22, 95% CI = 0.98-1.53). 79 Whether insulin and IGF are involved in the transition from MGUS to myeloma is a topic worthy of further exploration.…”
Section: Growth Factors and Cytokinesmentioning
confidence: 99%